The accuracy assessment of presepsin (sCD14-ST) for mortality prediction in adult patients with sepsis and a head-to-head comparison to PCT: a meta-analysis - Zhu Y; Li X; Guo P; Chen Y; Li J; Tao T (Dove Medical Press, 2019)
Ying Zhu,1,2 Xuehui Li,1 Peiyan Guo,1 Yuhan Chen,3 Jiandong Li,1 Tianzhu Tao41Department of Respiratory Medicine, The Seventh Medical Center of PLA General Hospital, Beijing, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Shanghai East Hospital, Tongji University, Shanghai, People’s Republic of China; 3Affiliated BaYi Children’s Hospital, The Seventh Medical Center of PLA General Hospital, Beijing, People’s Republic of China; 4Department of Anesthesiology, Air Force Medical Center, PLA, Beijing, People’s Republic of ChinaObjective: The soluble cluster of differentiation 14 subtype (sCD14-ST) or presepsin has recently been identified as a promising biomarker in sepsis. The present meta-analysis is performed to assess the prognostic value of presepsin in septic patients. Further, we compare the prognostic performance between presepsin and procalcitonin (PCT) in predicting all-cause mortality in these patients.Methods: A systemic and comprehensive search was conducted in PubMed, Embase and Cochrane databases by using Exploded Medical Subject Headings and appropriate corresponding keywords. Studies were eligible if they assessed the prognostic value of presepsin in sepsis and provided sufficient information to construct a 2×2 contingency table. A bivariate meta-analysis model was used to calculate the pooled sensitivity, specificity, positive/negative likelihood ratios and diagnostic odds ratio. The Chi-square and I2, index were used to assess the heterogeneity and inconsistency. The Deek’s funnel plot asymmetry test was used to assess the likelihood of publication bias.Results: Nine publications, comprising 1,561 patients, were included in this study. The overall area under the receiver operating characteristic curve (AUROC) of presepsin was 0.77 (95% CI, 0.73–0.81) with a pooled prognostic sensitivity (SEN) and specificity (SPE) of 0.83 (95% CI, 0.72–0.90) and 0.69 (95% CI, 0.63–0.74), respectively. Additionally, the PLR, NLR and DOR of presepsin were 2.6 (95% CI, 2.1–3.3), 0.25 (95% CI, 0.15–0.44) and 10 (95% CI, 5–22), respectively. The AUROC of PCT was 0.81 (95% CI, 0.78–0.84) with a pooled SEN of 0.76 (95% CI, 0.55–0.89) and SPE of 0.74 (95% CI, 0.33–0.94). There is no statistically significant difference in the performance of pooled SEN and SPE between presepsin and PCT, with a p value of 0.39 and 0.71, respectively.Conclusions: Based on the results of this meta-analysis, both presepsin and PCT are promising biomarkers for the prognosis of mortality in sepsis.Keywords: presepsin, sCD14-ST, procalcitonin, prognostic, sepsis, mortality